Illocutionary Act Used By Muniba Mazari In Inspirational And Motivational Video On Youtube - Ahmad Saputra (PIKTORIAL : Journal of Humanities, 2020)
This study aimed explaining the pragmatic study of the follow-up, which is about the types of action, direct or indirect language and the context of speech used in Muniba Mazari in motivational videos on YouTube. It is expected to provide insight to the reader about types of illocutionnary act in order to improve pragmatic competence. The research was presented in a qualitative form because the data were presented in sentence form. The data were collected from Muniba Mazari’s speech. This research also applies the theory of J. R Searle (1979) on the follow-up to identify the types of follow-up, context, and meaning of sentences. Further, this study used the theory of Geogre Yule (1996) to know the language style directly or indirectly.  The results of this study showed that there were 44 data found in the video of Muniba Mazari. They are: telling (3), claiming (3), sating (4), affirming (7), describing (9), suggesting (2), commanding (2), warning (3), vowing (3), promising (3), declaring (1), thanking (3), disliking (1). The most dominant in Muniba Mazari’s speech were representatives. It is because Muniba often reveals and informs about her life story to motivate the audience. Keywords: pragmatic, Illocutionary act, stydirect speech act, indirect speech acts